The Issue of Imminence: Can the Threat of a Cyber-Attack Invoke the Right to Anticipatory Self-Defence under International Law? - Samantha Shahriar (UCL Journal of Law and Jurisprudence, 2020)
To download this paper, please click here. As States increasingly rely on cyber technology, the threat of international cyberattacks perpetrated by States and non-State actors continues to grow. To lawfully use force in anticipation of a cyber-attack, it is crucial that the potential attack qualifies as an ‘armed attack’ under Article 51 of the UN Charter. The prospective cyber-attack also needs to be ‘imminent’. Despite there being consensus over some cyber-attacks rising to the level of an ‘armed attack’, it is nonetheless unclear — both theoretically and practically — whether cyber-attacks can be ‘imminent’. This article applies two approaches of ‘imminence’ to the context of cyber warfare to determine whether anticipatory self-defence can be invoked in these instances. Indeed, as detection capabilities amongst technologically advanced States continues to develop, it is more likely for cyber-attacks which qualify as ‘armed attacks’ to be detected far in advance. Thus, in providing this theoretical analysis of ‘imminence’, it will be established whether, in practice, the ‘last possible window’ in which to stop a prospective cyber-attack has already passed, or is likely to close. This article submits that due to a myriad of complex reasons, it remains unviable for States to invoke the right to anticipatory self-defence in response to a prospective cyber-attack.